Intesa Cgil-Sunia. . Circ. n.3799 - Segreteria: E. Ceremigna, G. Rastrelli, D. Turtura; Segreteria del Sunia: A. Bordieri, S. Bartocci; Organizzazione
note: all.: Documento di intesa tra Cgil e Sunia, 20 lug. 1984. destinatario: camere del lavoro territoriali